2011
DOI: 10.1167/10.1.8
|View full text |Cite
|
Sign up to set email alerts
|

The reference frame of the tilt aftereffect

Abstract: Perceptual aftereffects provide a sensitive tool to investigate the influence of eye and head position on visual processing. There have been recent indications that the TAE is remapped around the time of a saccade to remain aligned to the adapting location in the world. Here, we investigate the spatial frame of reference of the TAE by independently manipulating retinal position, gaze orientation, and head orientation between adaptation and test. The results show that the critical factor in the TAE is the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(127 citation statements)
references
References 49 publications
9
109
6
Order By: Relevance
“…However, if they are correct, there should be no spatiotopic after-effects, since that would indicate remapping of stimulus features. As pointed out by Cavanagh et al [96], a number of studies have indeed failed to show spatiotopic after-effects [82,[97][98][99]. However, there are also several studies that have shown clear spatiotopic after-effects [37,81,100,101] and trans-saccadic integration of object features [35,36].…”
Section: Remapping and Attention: Alternative Interpretationsmentioning
confidence: 98%
“…However, if they are correct, there should be no spatiotopic after-effects, since that would indicate remapping of stimulus features. As pointed out by Cavanagh et al [96], a number of studies have indeed failed to show spatiotopic after-effects [82,[97][98][99]. However, there are also several studies that have shown clear spatiotopic after-effects [37,81,100,101] and trans-saccadic integration of object features [35,36].…”
Section: Remapping and Attention: Alternative Interpretationsmentioning
confidence: 98%
“…If a saccade is made after adaptation, a tiltadaptation aftereffect cannot only be found at retinotopic locations but, critically, also at spatiotopic locations (Melcher, 2005(Melcher, , 2007, indicating remapping of visual features. However, other studies (Afraz & Cavanagh, 2009;Knapen, Rolfs, Wexler, & Cavanagh, 2010;Mathôt & Theeuwes, 2013) have failed to reveal spatiotopic aftereffects, but found only aftereffects of a retinotopic nature. Thus, until visual feature remapping can be demonstrated beyond dispute, a surface-feature blanking effect provides a challenge for cancellation accounts of visual stability.…”
mentioning
confidence: 93%
“…In particular, it has been suggested that the TAE is driven by retinotopic as well as cortical mechanisms (Knapen et al, 2010;Mathot and Theeuwes, 2013). This possibility is controversial because a retina-based mechanism would be unable to account for differences in the TAE caused by ecstasy consumption (Brown et al, 2007;Murray et al, 2012) or by tryptophan depletion (Masini et al, 1990).…”
Section: Discussionmentioning
confidence: 99%